ANALISIS INVESTASI PERGANTIAN WATER METER PELANGGAN PADA PERUSAHAAN DAERAH AIR MINUM KABUPATEN LOMBOK TENGAH - Fathurrahman, Fathurrahman (Nusantara Hasana Journal, 2021)
This research entitled "Analysis of Investor's Substitution of Water Meter at Regional Water Company of Central Lombok Regency", the purpose of this research is To analyze the feasibility of customer water meter turnover to the increase of income made by Regional Water Company of Central Lombok Regency. This research uses Discount Payback Period (DPP), Net Present Value (NPV), and Internal Rate of Return (IRR) analyzer. The type of research used is descriptive with data collection method that is case study concerning installation of customer water meter at PDAM Regency of Central Lombok, and technique of data collecting done by interview and documentation. Payback Period calculation results obtained shorter payback period ie 2 years 6 months 8 days from 5 years economic life. Net Present Value calculation results obtained results Rp3.840.112.160, -. This means that the investment plan of water mater in PDAM of Central Lombok Regency is profitable and feasible to be implemented. While the results of calculations using Internal Rate of Return method obtained by 86%, where the IRR results greater than the Cost of Capital is 20% so that investment can be accepted.